Impact of select immunologic and virologic biomarkers on CD4 cell count decrease in patients with chronic HIV-1 subtype C infection: results from Sinikithemba Cohort, Durban, South Africa. - Brumme, Z; Wang, B; Nair, K; Brumme, C; de Pierres, C; Reddy, S; Julg, B; Moodley, E; Thobakgale, C; Lu, Z; van der Stok, M; Bishop, K; et al. (2009)
BACKGROUND: The extent to which immunologic and clinical biomarkers influence human immunodeficiency virus type 1 (HIV-1) infection outcomes remains incompletely characterized, particularly for non-B subtypes. On the basis of data supporting in vitro HIV-1 protein-specific CD8 T lymphocyte responses as correlates of immune control in cross-sectional studies, we assessed the relationship of these responses, along with established HIV-1 biomarkers, with rates of CD4 cell count decrease in individuals infected with HIV-1 subtype C. METHODS: Bivariate and multivariate mixed-effects models were used to assess the relationship of baseline CD4 cell count, plasma viral load, human leukocyte antigen (HLA) class I alleles, and HIV-1 protein-specific CD8 T cell responses with the rate of CD4 cell count decrease in a longitudinal population-based cohort of 300 therapy-naive, chronically infected adults with baseline CD4 cell counts >200 cells/mm(3) and plasma viral loads >500 copies/mL over a median of 25 months of follow-up. RESULTS: In bivariate analyses, baseline CD4 cell count, plasma viral load, and possession of a protective HLA allele correlated significantly with the rate of CD4 cell count decrease. No relationship was observed between HIV-1 protein-specific CD8 T cell responses and CD4 cell count decrease. Results from multivariate models incorporating baseline CD4 cell counts (201-350 vs >350 cells/mm(3)), plasma viral load (< or =100,000 vs >100,000 copies/mL), and HLA (protective vs not protective) yielded the ability to discriminate CD4 cell count decreases over a 10-fold range. The fastest decrease was observed among individuals with CD4 cell counts >350 cells/mm(3) and plasma viral loads >100,000 copies/mL with no protective HLA alleles (-59 cells/mm(3) per year), whereas the slowest decrease was observed among individuals with CD4 cell counts 201-350 cells/mm(3), plasma viral loads < or =100,000 copies/mL, and a protective HLA allele (-6 cells/mm(3) per year). CONCLUSIONS: The combination of plasma viral load and HLA class I type, but not in vitro HIV-1 protein-specific CD8 T cell responses, differentiates rates of CD4 cell count decrease in patients with chronic subtype-C infection better than either marker alone.